PENGARUH LATIHAN LINGKARAN SPRINT TERHADAP KETERAMPILAN MENGGIRING BOLA PADA SSB PEKANBARU JUNIOR - Angga Gusrianto; Slamet '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT: The problems raised in this research is dribbling skills are less well as frequent loose ball as it passes the opponent, the ball is in the opponent seized, lack of ability driblling quickly, lack of skill dribble well. This research is a study with experimental treatment (Experimental), the population in this study is SSBpekanbaru junior athletes. sample in this study is a population which numbered 12 people. The technique can capture data from the pre-test and post-test. The instruments used in this research is aimed herding skills test to measure the ability to driblling. As the independent variable is linkaran sprint (X), while the dependent variable is dribbling skills (Y). After that, the data is processed with statistical, normality test with Liliefors test at significant level 0,05α. The hypothesis is there is influence their circle drill sprint towards dribbling skills on ssb junior pekanbaru. Based on t test analysis produces Thitung of 6.298 and 1.796 Ttabel means Thitung> Ttabel. It can be concluded that Ha is accepted, it concludes that there is significant influence from the circle drill sprint dribbling skills on ssb junior pekanbaru.Keywords: Circle Sprint Training, Driblling